Bond graph model-based fault detection and isolation of loaded Jeffcott Rotor system - Ma, Shiao (2009)
Rotating machineries are commonly used in the industry and in our daily life. A bond graph model based fault detection and isolation of rotating machinery is proposed in this research. A simple and effective bond graph model is developed for Jeffcott rotor integrated with some rotational loads. The model is further developed into a diagnostic bond graph model to generate residuals for the purpose of fault detection and isolation. The proposed method is verified by simulation using Matlab/simulink and by experiment using machinery fault simulator. It is shown that the proposed method can be successfully applied to the machinery fault simulator to detect and isolate imbalance fault, loose belt fault and three sensors’ fault. The proposed method has potential to be applied to real life rotating machinery.